Millennials' Marriage Readiness: The Role of Marriage Perceptions and Social Support - Wilis, Anastasia Putri Leleng; Satiadarma, Monty P.; Roswiyani (Psyche 165 Journal, 2025)
Globalization has caused significant changes in the lifestyle patterns of young adults, including a decline in marriage rates, especially among the Millennial generation. In Indonesia, many Millennials are delaying or even not considering marriage. Therefore, it is important to understand the factors that influence marriage readiness. This study aims to analyze the influence of marriage perceptions and social support on marriage readiness among the Millennial generation. The method used in this study is quantitative, involving 775 unmarried individuals aged 28–43 years. The instruments used for collection were The Marital Readiness Scale to measure marriage readiness, Marriage Perception Scale to measure marriage perceptions, and Multidimensional Scale of Perceived Social Support to measure social support. The results of the analysis using Pearson correlation showed a significant positive relationship between marriage perceptions and marriage readiness ( r = 0.480), as well as between social support and marriage readiness ( r = 0.542). In addition, linear regression analysis showed that marriage perceptions contributed 23% to marriage readiness, while social support contributed 29%. These findings suggest that positive views of marriage and adequate social support can improve marriage readiness among Millennials, leading to a more stable and harmonious marriage. Improved marriage readiness can contribute to happier and longer-lasting marriages. Therefore, interventions to improve perceptions and social support may be effective strategies in preparing Millennials for successful marriages.